Advanced Cardiac Models: Considerations for the Bioengineering of Advanced Cardiac In Vitro Models of Myocardial Infarction (Small 15/2021). Issue 15 (15th April 2021) - Sharma, Poonam; Wang, Xiaowei; Ming, Clara Liu Chung; Vettori, Laura; Figtree, Gemma; Boyle, Andrew; Gentile, Carmine
Abstract : In article number 2003765, Carmine Gentile and co‐workers describe the major pathophysiological features required for the bioengineering of a heart attack in a Petri dish. The article presents a thorough comparison of current in vitro, ex vivo, and in vivo models. It also explores the potential use of latest technologies for advanced cardiac models, such as 3D bioprinting, microfluidic devices and patient‐derived stem cell, with the potential to develop personalized novel therapies for heart attack patients.